When does higher credit lower forest area? Amazon contexts change credit’s impacts - Patricia G. C. Ruggiero; Paula Carvalho Pereda; Alexander Pfaff (Proceedings of the National Academy of Sciences, 2026)
Economic activities have transformed over half of the Earth’s surface and the large-scale conversion of rural forests to agropastoral production is ongoing. Raising access to credit may lead producers to expand at the expense of the forest or, instead, invest to raise yields, reducing forest loss per unit output. Looking across Brazil’s enormous Amazon, we show that extremely different local contexts differ in terms of which effect of credit dominates. We distinguish those contexts using factors that affect cattle and crop production. For each of these two outputs, we find distinct credit impacts by context. Cattle credit raises deforestation where pasture expands over native forest on far frontiers. Crop credit raises deforestation where farms expand over pasture and forest remnants. Understanding impacts heterogeneity can help to reduce losses of rural forests, even while credit is supporting local economies.